2017
DOI: 10.3389/fncel.2017.00149
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Mitochondrial Glutamate Carrier SLC25A22 in Astrocytes Leads to Intracellular Glutamate Accumulation

Abstract: The solute carrier family 25 (SLC25) drives the import of a large diversity of metabolites into mitochondria, a key cellular structure involved in many metabolic functions. Mutations of the mitochondrial glutamate carrier SLC25A22 (also named GC1) have been identified in early epileptic encephalopathy (EEE) and migrating partial seizures in infancy (MPSI) but the pathophysiological mechanism of GC1 deficiency is still unknown, hampered by the absence of an in vivo model. This carrier is mainly expressed in ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 74 publications
2
33
0
Order By: Relevance
“…Mitochondrial metabolic inhibitors have been reported to activate a mitochondrion-to-nucleus stress signaling network that leads to alterations in gene expression, which affects a wide variety of cellular processes. Mitochondria are key organelles for cellular bioenergetics and constantly undergo dynamic remodeling processes, and increased production of reactive oxygen products is associated with a variety of human disorders (Goubert et al, 2017). Moreover, there is a lack of research on mitochondrial metabolism in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial metabolic inhibitors have been reported to activate a mitochondrion-to-nucleus stress signaling network that leads to alterations in gene expression, which affects a wide variety of cellular processes. Mitochondria are key organelles for cellular bioenergetics and constantly undergo dynamic remodeling processes, and increased production of reactive oxygen products is associated with a variety of human disorders (Goubert et al, 2017). Moreover, there is a lack of research on mitochondrial metabolism in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…The ammonium enters the urea cycle for clearance of excess nitrogen, whereas 2-oxoglutarate is used in gluconeogenesis (in liver and kidney) or oxidized in TCA cycle for ATP production (in non-hepatic tissues). SLC25A22 is highly expressed in most tissues including the brain, especially in areas associated with motor coordination and in astrocytes, that control the uptake of extracellular neurotransmitter glutamate [147,148]. It is likely that extracellular glutamate levels in brain are dysregulated in SLC25A22 deficiency patients [143] because it was shown that (i) reduced expression of SLC25A22 in glial cells leads to intracellular glutamate accumulation [148], and (ii) aberrant glutamate catabolism in astrocytes is associated with altered clearance of extracellular (synaptic) glutamate and early epileptic encephalopathy [149].…”
Section: Slc25a22 (Glutamate Carrier 1 Gc1) Deficiencymentioning
confidence: 99%
“…SLC25A22 is highly expressed in most tissues including the brain, especially in areas associated with motor coordination and in astrocytes, that control the uptake of extracellular neurotransmitter glutamate [147,148]. It is likely that extracellular glutamate levels in brain are dysregulated in SLC25A22 deficiency patients [143] because it was shown that (i) reduced expression of SLC25A22 in glial cells leads to intracellular glutamate accumulation [148], and (ii) aberrant glutamate catabolism in astrocytes is associated with altered clearance of extracellular (synaptic) glutamate and early epileptic encephalopathy [149]. Moreover, some patients with SLC25A22 deficiency manifest hyperprolinemia [150], which might be explained by assuming that dysfunctional GC1 activity diminishes or abolishes the export of proline-derived glutamate from mitochondria leading to accumulation of proline in the body.…”
Section: Slc25a22 (Glutamate Carrier 1 Gc1) Deficiencymentioning
confidence: 99%
“…It catalyzes the glutamate/H+ symporter in order to transport glutamate into the mitochondria [184]. The dysregulation of extracellular glutamate and the activation of the extrasynaptic glutamate receptors would result from an absence of a functional SLC25A22 protein [185]. To date, 16 patients with EIEE3 have been reported [182][183][184]186,187].…”
Section: Epileptic Encephalopathy Early Infantile 3 (Omim #609304)mentioning
confidence: 99%